Certificate of Accreditation for Programme Master of Environmental Management (Development Planning) - Universiti Malaysia Sarawak (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Certificate of Accreditation for Programme Master of Environmental Management (Development Planning) has attained the quality assurance standards set by the agency and is in compliance with the Malaysian qualifications framework Level 7. Date of Accreditation : 11/09/2013